Potential effects of surface ozone on forests in Gangwon Province, South Korea, based on critical thresholds - Kim, Myeong-Ju; Lee, Sang-Deok (Frontiers in Forests and Global Change, 2022)
High hourly concentrations of ozone, a secondary pollutant produced from the photochemical reactions of primary precursors, have been increasing in South Korea, bringing potential adverse effects on vegetation. Deforestation caused by high ozone concentrations has been investigated in China and Japan. Using ozone measurements from East and West, Gangwon Province, South Korea, from 2001–2018, this study compared changes in surface ozone concentrations and analyzed the influences of meteorological factors and air pollutants. This study calculated accumulated ozone exposure over a threshold of 40 ppb (AOT40) and investigated the possibility of ozone affecting deforestation. Monthly average surface ozone concentrations increased rapidly in both regions from 2009. Although the daily total insolation (a meteorological factor that significantly impacts photochemical reactions) of West Gangwon and East Gangwon did not differ significantly, the ozone concentration was lower in East Gangwon than in West Gangwon (1.5 times lower from 2001–2018) owing to local strong winds. Moreover, there was a negative correlation between nitrogen Dioxide and ozone generation. AOT40 in West Gangwon was about twice that in East Gangwon and exceeded 10,000 ppbh, the critical level for forests, every year since 2003. Potential damage from high concentrations of ozone was higher in West Gangwon than in East Gangwon.